Land Cultivation Rights on Indicated Abandoned Land in Western Aceh Regency (Identification of Causal Factors and Legal Aspects of the Settlement) - Ilyas Ismail; Abdurrahman Abdurrahman; Yunita Yunita (Proceedings of AICS - Social Sciences, 2017)
This research aims to identify and explain the causative factors of unutilized land with its Cultivation Right (HGU) and legal aspects of abandoned land settlement. There are 119.400 ha (31.48%) abandoned land of 379.374,02 ha HGU in Aceh Province. This condition is important to be concerned since the national government and the local government of Aceh has the same vision to increase the farmer’s welfare through the government strategic program “Agrarian Reform”, which has the main objective to redistribute assets related land in order to decrease the economic gap in the country. Therefore, this research is important to be conducted in order to understand the possible alternative ways to curb and use of HGU, which is identified as abandoned land. The results show that there are four factors that cause land unexploited with its HGU, namely: the land is used for supporting facilities; the physical condition of the land, which cannot be utilized; the land is used as a reserved area; and possible dispute that may occur. There are several regulations of indicated abandoned land settlement: first, the inventory of land of rights or basic tenure of indicated abandoned land; second, identification and research of indicated abandoned land; third, warning against rights holders; and last, the determination of the abandoned land. Land with HGU that is indicated to be abandoned in Western Aceh, identifications and research have been conducted and none have been designated as abandoned land.